2009
DOI: 10.1245/s10434-009-0867-9
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Role of Taurolidine in Cancer Therapy

Abstract: Taurolidine induces cancer cell death through a variety of mechanisms. Even now, all the antineoplastic pathways it employs are not completely elucidated. It has been shown to enhance apoptosis, inhibit angiogenesis, reduce tumor adherence, downregulate proinflammatory cytokine release, and stimulate anticancer immune regulation following surgical trauma. Apoptosis is activated through both a mitochondrial cytochrome-c-dependent mechanism and an extrinsic direct pathway. A lot of in vitro and animal data suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 62 publications
0
54
0
1
Order By: Relevance
“…Furthermore, apoptotic cells can be observed morphologically following Tau treatment (14). Tau can also function as an antitumor agent by downregulating the expression of matrix metalloproteinase-2, upregulating N-acetylgalactosaminyltransferase, and inhibiting the potential invasion and metastasis induced by ionizing radiation (13). In a previous study, Tau was shown to induce the apoptosis of human colon cancer cells by upregulating the expression of the p53 upregulated modulator of apoptosis (PUMA) gene, independent of p53 (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, apoptotic cells can be observed morphologically following Tau treatment (14). Tau can also function as an antitumor agent by downregulating the expression of matrix metalloproteinase-2, upregulating N-acetylgalactosaminyltransferase, and inhibiting the potential invasion and metastasis induced by ionizing radiation (13). In a previous study, Tau was shown to induce the apoptosis of human colon cancer cells by upregulating the expression of the p53 upregulated modulator of apoptosis (PUMA) gene, independent of p53 (15).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, serum Tau levels in patients with breast cancer have been found to be significantly lower compared with those in high-risk and control groups. Thus, Tau may become a novel indicator for the early diagnosis of breast and bladder cancers (11)(12)(13). The study of tumor prevention and treatment with Tau is nascent.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Tau as an effective antioxidant may hinder an increase in reactive oxygen species in tumors, thereby reducing the development of cancer (9). In addition, Tau could have anti-tumor activity by downregulation of MMP-2, upregulation of N-acetylgalactosaminytransferase, and inhibition of the potential invasion and metastasis induced by ionizing radiation (10).…”
Section: Introductionmentioning
confidence: 99%
“…Taurolidine was well-tolerated, and encouraging initial results were reported in patients with pancreatic and stomach cancer, colo-rectal cancer and tumors of the central nervous system. [10][11][12] Yours sincerely, C. Braumann R. W. Pfirrmann…”
Section: To the Editormentioning
confidence: 99%